Performance Analysis of STIE Lecturers in LLDIKTI Region III Jakarta - Riadi, Refren; Wibowo; Gustari, Irvandi (Jurnal Bisnis dan Ekonomi, 2024)
Objective: This research aims to identify factors that influence lecturer performance and develop a model that can explain the relationship between achievement motivation, lecturer competence, organizational commitment, and job satisfaction with the performance of permanent lecturers in seven higher education schools in Region III Jakarta. Methodology: This research applies the Partial Least Squares Structural Equation Modeling (PLS-SEM) method involving 189 respondents who were randomly selected through questionnaire distribution with a 1-5 Likert scale . Research results: analysis results, lecturer performance can be explained by Achievement Motivation, Organizational Commitment, and Competence, with Lecturer Organizational Commitment being the most dominant variable. This research presents novelty through the application of a model that has never been used before in Lecturer Performance case studies, which integrates variables and dimensions from previous research. Although there have been many studies discussing Achievement Motivation, what is unique is that this research shows a negative and significant influence on Job Satisfaction. Apart from that, Job Satisfaction does not function as a mediator between lecturers' Achievement Motivation, Competence and Organizational Commitment on lecturers' performance.